1917-JÍLǴÍ FEVRAL REVOLYUCIYASÍ HÁM TÚRKSTANDAǴÍ KOLONIALLÍQ BASQARÍW SISTEMASÍNÍŃ KRIZISI - Qurbaniyazova, Ayzada Pulatovna (SCIENCE and SOCIETY, 2026)
The article analyzes the political situation in the Turkestan region on the eve of the February Revolution of 1917 and the crisis state of the Russian Empire’s "military-people’s rule" system. Historical objectivity, systematic analysis, and comparative-historical methods were used in the research process. It was emphasized that the interim government’s inability to renounce its colonial legacy was the primary factor leading to the transfer of power to radical forces.